SANTEN-fuse AS ANEARTHQUAKE DAMPER FOR PENDOPO JOGLO - Bisatya W., MAER; Pamuda, PUDJISURYADI (DIMENSI (Journal of Architecture and Built Environment), 2015)
The 2006 Yogyakarta earthquake resulted in collapse of several traditional buildings in Yogyakarta, including joglos. This fact indicates that joglos are quite vulnerable to low-frequency ground shaking. The stability and rigidity of a joglo building are provided by the core of the building, i.e. the rong-rongan structure, in which connection of sakaguru (the column)-sunduk (the long span beam)-kili (the short span beam) has a rigid characteristic. This rigid rong-rongan structure behaves elastically during an earthquake event, and attracts large inertia force. This research aims to increase the structure performance of the rong-rongan by adding “SANTEN-fuse,” an earthquake vibration damper, and by changing the joint connection of sakaguru-sunduk-kili to be that of a pin connection, but not changing the physical appearance of rong-rongan. Santen, whose function is to transfer the load of the roof from blandar to sunduk and from pangeret to kili, is modified so that it has frictional damper characteristic. This “SANTEN-fuse” can resist shear force up to certain level before it slides and acting as a damper. With the reduced stiffness, which leads to reduced inertia force, the overall structural responses are expected to be lower. An experimental quantitative method was used by doing a simulation using SAP2000 software to verify the idea. The pendopo dalem Yudonegaran a joglo house in Yogyakarta was chosen as a case study. Non-linear time history analysis was conducted. Simulation results showed that the proposed modification of rong-rongan structure by using “SANTEN-fuse”, performed better than the original rong-rongan structure.